2014
DOI: 10.1074/jbc.m114.573972
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of Uba5 Enzyme and the Ufm1 Conjugation Pathway

Abstract: Background: Human ubiquitin-like protein Ufm1 and its activating enzyme, Uba5, are involved in endoplasmic reticulum (ER) stress response. Results: The Uba5-Ufm1 conjugation pathway is characterized in both reconstituted systems and cellular settings. Conclusion: Uba5 activates Ufm1 via a distinct two-step mechanism. Significance: This study represents the first mechanistic characterization of Uba5, a homodimeric member of the E1 enzyme family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…That, therefore, suggests that binding of UFC1, similar to UFM1, can stabilize the dimeric UBA5 and thereby assist in ATP binding. Indeed, previously, Gavin et al (32) demonstrated that UFC1 stimulates the formation of the UBA5 to UFM1 thioester.…”
Section: Discussionmentioning
confidence: 92%
“…That, therefore, suggests that binding of UFC1, similar to UFM1, can stabilize the dimeric UBA5 and thereby assist in ATP binding. Indeed, previously, Gavin et al (32) demonstrated that UFC1 stimulates the formation of the UBA5 to UFM1 thioester.…”
Section: Discussionmentioning
confidence: 92%
“… 89 , 139 This would facilitate the formation of an E1∼UFM1 thioester, a process that is also stimulated by binding of E2 UFC1 . 141 Contrary to canonical E1s, UBA5 does not undergo a second round of adenylation following thioester formation. 141 However, thioester transfer is accelerated by E1 UBA5 binding of ATP and magnesium.…”
Section: E1 Activating Enzymesmentioning
confidence: 99%
“… 141 Contrary to canonical E1s, UBA5 does not undergo a second round of adenylation following thioester formation. 141 However, thioester transfer is accelerated by E1 UBA5 binding of ATP and magnesium. 141 Similar to E1 ATG7 , thioester transfer of UFM1 from E1 UBA5 to E2 UFC1 was shown to occur via a trans mechanism.…”
Section: E1 Activating Enzymesmentioning
confidence: 99%
“…Although the only step in UFM1 conjugation that requires energy is UFM1 activation by UBA5, ATP also plays a role in the transfer of UFM1 from UBA5 to UFC1. Specifically, Gavin et al have shown that charged UBA5 (UBA5~UFM1) hardly transfers UFM1 to UFC1 if ATP is missing [37]. In that case hydrolysis of ATP is not required but only binding of ATP to the UBA5~UFM1 adduct.…”
Section: The N-terminus Of Uba5 Contributes To the Transfer Of Ufm1 Fmentioning
confidence: 99%